THEMATIC GROUPS OF PROVERBS WITH FLOWER COMPONENT IN ENGLISH AND UZBEK LANGUAGE - Abdukayumova Sanobar Abdurashidovna (World Scientific Research Journal, 2025)
Abstract. The regulation of language-related issues has been a practical and theoretical issue for many centuries. The work on thematic grouping of proverbs from the roof of humanity is extensive and diverse. There is no aspect of society and nature that has not been reflected in the themes of proverbs. They include everything from the life experience of mankind, lifestyle, national spirit and problems, to the characteristics of the animal and plant world.